ESTUDIO ECONÓMICO PARA LA APERTURA DE UNA SUCURSAL DE LA COOPERATIVA DE AHORRO Y CRÉDITO SANTIAGO LTDA. EN LA CIUDAD DE LOJA - Ordóñez Quezada., Mercedes Rossio (2019)
The ECONOMIC STUDY FOR THE OPENING OF A BRANCH OF THE SANTIAGO LTDA SAVINGS AND CREDIT COOPERATIVE, IN THE CITY OF LOJA, was developed with the purpose of knowing the viability of the project with the purpose of carrying out an economic study that allows to get to know the total value of the investment with which you can open a branch of the COAC "Santiago", in the city of Loja. the same that will provide financial products and services to the community, fulfilling each of the economic needs required by the inhabitants in such a way that it helps the economic strengthening of the population. In order to meet the objectives set out, a market study was carried out in which supply and demand are analyzed. The survey was applied to the population with a sample of 91 people, the results obtained allowed reaching conclusions, and through These are the recommendations that are intended to know the viability of the project for the opening of the branch; the technical study was carried out where the location and the optimal size of the project were determined, then in the result of the economic study the results of the administrative costs were obtained which is of $ 28,895.81, sale costs of $ 2,100.00 and the financial costs of $ 4,037.64, in the fixed investment a result of $ 5,831.61 was obtained and in the deferred investment $ 3,881.36 and considering other factors as current assets with a value of $ 2,582.99 and the financial capital of $ 25,521.05, that is to say that the cooperative 5 needs a total investment of $ 37,817.00, according to the financing sources, financing was chosen with third parties with Bancodesarrollo for an amount of $ 12,295.95, for the preparation of the financial evaluation the break-even point was elaborated according to the sales giving me as a result of $ 36,693.61 and according to the installed capacity 72%, therefore I will have a negative NPV of $ -13,927.59, a TIR of - 15%, a to RCB of 0.37% and an investment recovery of 6 years, 9 months, 13 days, the analysis of sensitivity is explained that the increase in costs will be -41.33% and revenues decrease by 0.88% . With the realization of the economic study, it was announced the total amount of the investment $ 37,817.00, which will count for the opening of the branch, income generated by interest that will be of $ 50,534.23 and a profit of $ 4,094.28, results that reveal the economic and financial situation that can therefore be deduced that is not profitable since they present a low profit, it is not advisable to carry out the project of opening a branch of the COAC "Santiago ", Understanding that the cooperative must set evolution goals within reasonable periods of time to achieve the continuous increase directly with respect to the institutions that are the competencies and that are already working for some years in the market to try to match them in As soon as possible and over time think about gaining absolute market leadership.